Comparing immersive Virtual Reality to mobile applications in foreign language learning in higher education: a quasi-experiment - Nicolaidou, Iolie; Pissas, Petros; Boglou, Dimitrios (My University, 2021)
Virtual Reality applications are predicted to create a paradigm shift in education, but there is little empirical evidence of their educational value. Virtual Reality affordances to support language learning have not yet been realized. This quasi-experimental study investigated the effect of a Virtual Reality application on foreign language learning and compared engagement, engrossment, and immersion between two versions of the application (Virtual Reality and mobile). Twenty experimental group undergraduate students used a head-mounted Virtual Reality display and twenty control group students used a mobile application for learning Italian as a foreign language. Data sources included: (a) a 10 open-ended questions pre-test and post-test measuring vocabulary skills, and (b) a validated questionnaire with 21 seven-point Likert scale items measuring engagement, engrossment, and immersion. Findings revealed a statistically significant difference in the experimental group students’ vocabulary performance when students’ pre-test and post-test scores were compared. Engagement, engrossment, and immersion received relatively high scores by Virtual Reality participants. The study did not find a statistically significant difference between the two conditions. The study provides preliminary empirical data indicating that Virtual Reality applications can be both effective and engaging for language learning, even though they were not found to be superior to mobile applications.
Keywords: Immersion; Engrossment; Language learning; Virtual reality applications; Higher education; Engagement